Clinical Research on Adjustment Disorders due to Physical Diseases in Consultation-liaison Psychiatry: A trial of subclassification according to their experimental reaction patterns in the process of accepting their diseases - Sato, Naohiro; Kimura, Hiroyuki; Kimura, Tetsuya (Japanese Journal of General Hospital Psychiatry, 2011)
Patients with adjustment disorders due to physical diseases who were involved in the consultation-liaison area in a general hospital were subclassified into three groups according to their experimental reaction patterns in the process of accepting their diseases. A total of 71 subjects with adjustment disorders due to physical diseases, who were newly referred to the Department of Psychiatry from another department between April 2004 and December 2006, were evaluated. They were classified into three groups (simple type, release type, and conflict-displaying type) according to their experimental reaction patterns in the process of accepting their diseases, and representative cases were presented. The age, sex, symptoms, time from the onset to admission, duration of hospitalization, and prognosis were compared between the groups, and the clinical characteristics were described. Based on the features of each disease type, the clinical characteristics appeared to exhibit a close relationship with each other, and differ according to the severity of psychological distress involved in accepting diseases. Therefore, it was suggested that such subclassification can provide a useful viewpoint to understand patients going through disease acceptance.